Effects of plant cover on properties of rhizosphere and inter-plant soil in a semiarid valley, SW China. (March 2016) - Qu, Laiye; Huang, Yuanyuan; Ma, Keming; Zhang, Yuxin; Biere, Arjen
Abstract: Plant establishment is widely recognized as an effective way to prevent soil erosion in arid and semiarid ecosystems. Artemisia gmelinii, a pioneering species in many degraded ecosystems in China, is effective in improving soil properties and controlling runoff and soil loss, but mechanisms underlying soil improvement are not well understood. We therefore investigated how the presence and cover of A. gmelinii affect soil physico-chemical properties and soil microbial communities in differently sized soil aggregates in the rhizosphere and inter-plant soil in the Upper Minjiang River arid valley of China. We found that A. gmelinii presence significantly improved soil quality in terms of soil structure, water content, aggregate-associated carbon and nutrients, and soil microbial biomass and activities. Interestingly, also inter-plant soils were strongly influenced by adjacent-plant-cover, showing enhanced soil organic carbon, total carbon, nitrogen and phosphorus, and reduced soil bulk density and pH with increasing A. gmelinii cover in plots. In turn, the A. gmelinii -induced changes in inter-plant soil properties could explain a large part of the observed variation in microbial biomass, carbon and nitrogen. Importantly, effects of the presence and cover of A. gmelinii on soil properties were mostly specific for particular aggregate size classes. Specifically, A. gmelinii significantly increased P accumulation only in small macroaggregates (250–2000 μm) illustrating the importance of this aggregate class in terms of plant-mediated phosphorus accumulation, critical for P uptake in this P limited area. Our results thus indicate that A. gmelinii not only improves soil physical and microbial conditions in its rhizosphere but also in inter-plant soil, and that increasing A. gmelinii cover has the potential to reduce runoff and soil loss and to promote revegetation. Highlights: The shrub Artemisia gmelinii is used in restoration of degraded semi-arid regions of China. A. gmelinii presence increases phosphorus accumulation in small soil macro-aggregates. A. gmelinii improves soil physical and microbial properties in rhizosphere and inter-plant soil. Increasing A. gmelinii cover can reduce runoff and soil loss and promote revegetation.